Increase in Safe Zone Area of the Acetabular Cup Using Dual Mobility Cups in THA. Issue 4 (July 2017) - Ohmori, Takaaki; Kabata, Tamon; Maeda, Toru; Kajino, Yoshitomo; Taga, Tadashi; Hasegawa, Kazuhiro; Inoue, Daisuke; Yamamoto, Takashi; Takagi, Tomoharu; Tsuchiya, Hiroyuki
Background: Dual mobility cup (DMC) inserts reduce the risk of dislocation after total hip arthroplasty (THA). No available research has clearly delineated stability advantages of DMC inserts in primary and revision THA. We investigated: (i) the degree of change in the safe zone of the cup when a DMC insert is used compared to a fixed insert; (ii) the method of selecting candidates for a DMC insert without changing the position of the acetabular (cup) component during revision THA in frequent dislocation cases caused by implant impingement. Methods: A model of the pelvis and femur was developed from computed tomography images. The safe zone was defined as the area in the acetabular component, over which conditions for stable range of motion were satisfied. The safe zone was calculated for both a fixed and a DMC insert over a predetermined range of 3-D motion, and the effect of increasing the anteversion position of the femoral component from 5° to 35° was quantified. Results: The lowest ratio of the area of the safe zone was about 4.9 at 20° anteverison of the femoral component. Safe zone of DMC inserts zone had increased stability of 10°-15° in both vertical and horizontal directions, compared to fixed inserts. A 5- to10-fold expansion of the safe zone can be expected with the use of DMC insert. Conclusions: DMC insert could help to set the acetabular component more accurately in primary and revision THA.